Uji Produktivitas Jamur Merang (Volvariella volvaceae) Bibit F4 Asal Cilamaya Dengan Berbagai Konsentrasi Media Tanam Substitusi Tongkol Jagung - Safitri, Shasha Asyarita; Lestari, Ani (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2021)
The objective of this research was to get out the concentrations of the corn cob planting media that gives the highest result on the straw mushroom planting media. This research was conducted at plant Biotechnology Laboratory Faculty of Agriculture University of Singaperbangsa Karawang and Pasir Mulya Village, Majalaya, Karawang. Used in June to October 2020. This research used experimental method was used randomized block design single factor with four replications. There was 6 treatments: A (Control), B ( 5% corncob + 95% straw, C (10% corncob + 90% straw), D ( 15% corncob + 85% straw), E (20% corncob + 80% straw), and F (25% corncob + 75% straw). The effect of treatment with analiyzed of variance and if the F test level 5% was significant, then it continued with DMRT (Duncan Multiple Range Test) at the level of 5% to find out the best treatment. The result showed that they were not significant effect on the length, diameter, and weight. Bused on average of amount production in each treatment, treatment B showed the highest production during 1 planting period, namely 2,230 kg